Impact of Liquid Composition and Asphaltene Properties on Asphaltene Aggregation Using Interaction Energies. Issue 8 (18th June 2021) - Nategh, Mahshid; Mahdiyar, Hojjat; Malayeri, M. Reza; Unz, Simon; Beckmann, Michael
Abstract: An interaction energy model is employed to discern the roles of liquid composition and asphaltene properties on asphaltene stability. The model determines Lifshitz‐van der Waals (LW) and acid‐base (AB) for two asphaltenes of A and B types with different polarities and synthetic oils with different nC7 volume fractions. The results indicate that the liquid loses its solubility with increased nC7 volume fraction, due to the reduction in its electron donor component. Moreover, at the very beginning of nC7 addition, both asphaltenes show a similar resistance against aggregation, due to the similar rates of change in their LW and AB interaction energies. However, at latter stages of nC7 addition, the two asphaltenes tend to have different precipitation propensities, which is consistent with the results of UV‐vis measurements. Abstract : According to the interaction energy model, the role of nC7 in the reduction of asphaltene solubility is justified with the reduction in the basic power of the mixture. Asphaltene with stronger polar interaction between its components acts stronger against asphaltene‐liquid polar interaction and outweighs it at lower nC7 fractions.